Riwayat Surat Kabar Lokal Aman Makmur - Berliani, Riyona (Mahesa Research Center (PT. Mahesa Global Publishing), 2022)
Reporting on the fight against communism is important to restore the dignity of the Minangkabau people because the Minangkabau ethnic group has felt powerless since the PRRI's defeat. Aman Makmur is one of the short-lived newspapers in the midst of the political turmoil during the Guided Democracy period. However, his presence from 1963 until 1965 had more or less had an impact on the Minangkabau people who at that time felt powerless after the PRRI. In addition, Aman Makmur was not afraid to compete with the communist press, even though it was banned several times. The banning of Aman Makmur along with several other newspapers in 1965 was followed by the end of the Guided Democracy period.